PERAN ASPEK HUKUM DALAM PROSES PEMBANGUNAN DAN INOVASI DI PERUSAHAAN PADA ZAMAN DIGITAL - Andiani Sharfina; Elfrida Ratnawati Gultom (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This article examines the economic and legal aspects of companies' innovative activities in the context of the digital economy. The authors have stated that the company's innovative activities also include the development of artificial intelligence and robotics and that in the current conditions when creating and using artificial intelligence technologies, the issue of ensuring national security in the digital environment is of particular importance. In this case, the strategic objective of information security assurance is to protect the vital interests of individuals and society against internal and external threats related to the application of information technology for various purposes that are contrary to civil law. It is evident that innovation will increase the attractiveness of business investment, maintain a balance of creative freedom and internal control measures, self-regulate in the field of digital technology, and develop a unified legal framework in the economic space.